청주지역 대학생의 에너지 음료에 대한 인식과 섭취 실태 및 섭취 관련 요인 - 김태양(Tae Yang Kim); 김수민(Soo Min Kim); 김지연(Ji Yeon Kim); 임정연(Jeong Yeon Im); 우혜(Hui Yu); 한영희(Young-Hee Han); 현태선(Taisun Hyun) (Korean journal of community nutrition, 2018)
Objectives: This study was conducted to investigate the awareness of energy drinks, energy drink consumption behaviors, and associated factors among college students. Methods: A total of 536 students from three universities in Cheongju completed a self-administered questionnaire regarding awareness and consumption of energy drinks as well as general characteristics, health-related characteristics, and eating habits. Results: Approximately half of the respondents reported they knew what energy drinks were, while 45.7% had heard of energy drinks but did not know what they were. However, 76.9% had experience in using energy drinks. The main reason for using energy drinks was to stay awake, and the main place that they were used was on campus or at the library. More than 70% of energy drink users did not read the caffeine contents of energy drinks. After consuming energy drinks, 31.3% experienced adverse effects, the most serious being sleep disturbance. Approximately 33% of students consumed energy drinks once a month or more frequently, and men consumed energy drinks more frequently than females. Energy drink users who consumed at least one drink each month were more likely to be natural science major or drink more milk for male students, and to have more allowances or consume less meat for female students, compared with non-users. Conclusions: Our study showed that 33% of students consumed at least one energy drink each month, and there were a small number of students consumed energy drinks almost every day or energy drinks mixed with alcohol. Accordingly, college students should be taught potential health hazards of energy drinks mixed with alcohol as well as energy drinks alone. In addition, reading labels about caffeine and sugar contents in energy drinks is encouraged.